Comparative evaluation of galactomannan optical density indices and culture results in bronchoscopic specimens obtained from neutropenic and non‐neutropenic patients. Issue 3 (8th September 2013) - Ağca, Harun; Ener, Beyza; Yılmaz, Emel; Ursavaş, Ahmet; Kazak, Esra; Özkocaman, Vildan; Çetinoğlu, Ezgi Demirdöğen; Dilektaşlı, Aslı Görek; Akalın, Halis; Özkalemkaş, Fahir; Ali, Rıdvan
Summary Aspergillus infections are major causes of morbidity and mortality among immunocompromised patients. This study was designed to investigate the galactomannan assay optical density (OD) indices relative to the culture results in bronchoscopic samples obtained from neutropenic and non‐neutropenic patients. Galactomannan OD indices from 1427 samples from 2005 to 2012, which were sent from 839 patients and were composed of bronchial lavage (BL = 727) and bronchoalveolar lavage fluids (BAL = 700), were retrospectively analysed. The recovery rates of Aspergillus species from these specimens were 9.4% from the combined patient group and 13.3% from the neutropenic group. Aspergillus fumigatus complex was the most frequently isolated species. The mean and median OD indices of the positive and negative culture samples are approximately 5 and 1, respectively, and 91% of all culture‐positive samples have ≥1 OD index value. The receiver‐operating characteristics curve analysis demonstrated that the feasibility of the Aspergillus galactomannan assay and Aspergillus galactomannan test has superior accuracy in BAL compared to BL fluids, and the test is not affected by the immune status of the patient. We suggest that the Aspergillus galactomannan test, which uses bronchoscopic material, leads to an earlier diagnosis and if the OD index is found ≥1, fungal growth can be expected.